Missions as relational scales of agency: urban leverage for transformative change - Kalliomäki, Helka; Hämäläinen, Helmi; Kalliokoski, Johanna; Kunttu, Leena (Taylor & Francis, 2026)
The mission-oriented innovation policy literature has recently attempted to address implementation challenges and identified research needs around the role of cities, scales and agency in implementation. We address these gaps and contribute to the literature, particularly on the spatial governance of mission-oriented innovation policies, through an integrated theoretical framework conceptualising missions as relational scales of agency. A case study of the mobility as a service (MaaS) concept in Finland enables us to identify and discuss scalar tensions related to MaaS failures. We conceptualise those as leverage points for transformative change that underscore the potential of urban policies in integrated transformative mission implementation.
Keywords: Scale; mission-oriented innovation policy; agency; urban policy; leverage point; mobility as a service; fi=Aluetiede|en=Regional Studies|; fi=Aluetiede|en=Regional Studies|